2015
DOI: 10.1259/dmfr.20150098
|View full text |Cite
|
Sign up to set email alerts
|

Stationary intraoral digital tomosynthesis using a carbon nanotube X-ray source array

Abstract: Objectives: Intraoral dental tomosynthesis and closely related tuned-aperture CT (TACT) are low-dose three-dimensional (3D) imaging modalities that have shown improved detection of multiple dental diseases. Clinical interest in implementing these technologies waned owing to their time-consuming nature. Recently developed carbon nanotube (CNT) X-ray sources allow rapid multi-image acquisition without mechanical motion, making tomosynthesis a clinically viable technique. The objective of this investigation was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Continuous 2D images of different angles are imported to a computer for image reconstruction using digital tomosynthesis, allowing the reconstructed images of different depths to be observed. Although the prototype of this proposed system can obtain reconstructed images in different depths, the shooting time is over 10 min because current commercially available digital X-ray sensors are unable to continuously shoot at high frame rates, rendering them inapplicable to clinical dentistry [9][10][11]. Therefore, our team developed a high-frame-rate sensor in 2019 [12].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous 2D images of different angles are imported to a computer for image reconstruction using digital tomosynthesis, allowing the reconstructed images of different depths to be observed. Although the prototype of this proposed system can obtain reconstructed images in different depths, the shooting time is over 10 min because current commercially available digital X-ray sensors are unable to continuously shoot at high frame rates, rendering them inapplicable to clinical dentistry [9][10][11]. Therefore, our team developed a high-frame-rate sensor in 2019 [12].…”
Section: Introductionmentioning
confidence: 99%
“…These 2D projection images were reconstructed through tomosynthesis to obtain numerous slice images of different depths. Shan et al [10] and Inscoe et al [11, 12] used a carbon nanotube X-ray source array to develop stationary digital tomosynthesis for dental imaging. In their studies [1012], the feasibility of stationary intraoral tomosynthesis was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the potential implications of source array technology in dental imaging, stationary intraoral tomosynthesis (s-IOT) was proposed 29 and assessed using a benchtop CNT-source array (XinRay Systems, Morrisville, NC), dental phantoms and extracted teeth, and a standard intraoral detector (SuniRay2, Suni Medical Imaging, Inc., San Jose, CA, USA). 30 Various angular spans and dose distributions were explored to define the optimal imaging configuration. Using this benchtop device, a preliminary reader study compared the detection sensitivity of s-IOT and standard 2D intraoral radiography for interproximal caries in extracted human teeth, using micro-CT images as the ground truth.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the potential implications of source array technology in dental imaging, stationary intraoral tomosynthesis (s‐IOT) was proposed and assessed using a benchtop CNT‐source array (XinRay Systems, Morrisville, NC), dental phantoms and extracted teeth, and a standard intraoral detector (SuniRay2, Suni Medical Imaging, Inc., San Jose, CA, USA) . Various angular spans and dose distributions were explored to define the optimal imaging configuration.…”
Section: Introductionmentioning
confidence: 99%